2020
DOI: 10.1111/acer.14413
|View full text |Cite
|
Sign up to set email alerts
|

Can Alcohol Use Disorder Recovery Include Some Heavy Drinking? A Replication and Extension up to 9 Years Following Treatment

Abstract: Background Recent research indicates some individuals who engage in heavy drinking following treatment for alcohol use disorder fare as well as those who abstain with respect to psychosocial functioning, employment, life satisfaction, and mental health. The current study evaluated whether these findings replicated in an independent sample and examined associations between recovery profiles and functioning up to 6 years later. Methods Data were from the 3‐year and 7‐ to 9‐year follow‐ups of subsamples initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 68 publications
5
25
0
2
Order By: Relevance
“…These results generally concur with long‐term prospective studies of treatment and community samples of heavy drinkers that found positive drinking outcomes were accompanied by improved health, life satisfaction, and functioning (e.g., Moos & Moos, 2007; Witkiewitz, Pearson et al, 2020; Witkiewitz et al, 2019), and they have potential implications for assessment and treatment. First, assessing how persons with substance use disorders spend their money on substances and other commodities has utility for predicting behavior change outcomes and thus may inform treatment goals.…”
Section: Discussionsupporting
confidence: 80%
“…These results generally concur with long‐term prospective studies of treatment and community samples of heavy drinkers that found positive drinking outcomes were accompanied by improved health, life satisfaction, and functioning (e.g., Moos & Moos, 2007; Witkiewitz, Pearson et al, 2020; Witkiewitz et al, 2019), and they have potential implications for assessment and treatment. First, assessing how persons with substance use disorders spend their money on substances and other commodities has utility for predicting behavior change outcomes and thus may inform treatment goals.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, study findings support and extend a growing body of literature that suggests that abstinence is not the only path to achieve and/or sustain a high level of psychosocial functioning in the years following alcohol treatment. Rather, there appear to be multiple paths to recovery that can include moderate or heavy alcohol consumption post-treatment for some individuals 16,23,25,48 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study attempts to replicate and extend our recent work with the COMBINE Study 24 by investigating the relationships between recovery profiles identified at three years following treatment and alcohol consumption and psychological functioning outcomes at ten years following treatment among a site-specific subset of participants involved in Project MATCH 22 . Importantly, this is an extension of our analyses with COMBINE 25 to include a broader set of psychosocial functioning indicators, for a longer time period, and the analyses are conducted in a more diverse sample of participants. We hypothesized the recovery typologies characterized by high functioning heavy drinking and high functioning infrequent non-heavy drinking at three years following treatment 23 would be associated with less drinking and higher psychological functioning at ten years following treatment when compared to recovery typologies characterized by low functioning frequent or infrequent heavy drinkers at three years following treatment.…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that identity changes can occur independently of changes in patterns of substance use (Martinelli et al, 2020;Witkiewitz et al, 2019Witkiewitz et al, , 2020. Other researchers question the need for a change of social identity during the recovery process (e.g.…”
Section: Recovery and Identitymentioning
confidence: 99%